Effectiveness of bisphosphonate analogues and functional electrical stimulation on attenuating post-injury osteoporosis in spinal cord injury patients- a systematic review and meta-analysis. - Ke-Vin Chang; Chen-Yu Hung; Wen-Shiang Chen; Mei-Shu Lai; Kuo-Liong Chien; Der-Sheng Han (PLoS ONE)
Background Various pharmacologic and non-pharmacologic approaches have been applied to reduce sublesional bone loss after spinal cord injury (SCI), and the results are inconsistent across the studies. The objective of this meta-analysis was to investigate whether the two most-studied interventions, bisphosphonate analogues and functional electrical stimulation (FES), could effectively decrease bone mineral density (BMD) attenuation and/or restore lost BMD in the SCI population. Methods Randomized controlled trials, quasi-experimental studies, and prospective follow-up studies employing bisphosphonates or FES to treat post-SCI osteoporosis were identified in PubMed and Scopus. The primary outcome was the percentage of BMD change from baseline measured by dual-energy X-ray absorptiometry (DEXA) or computed tomography (CT). Data were extracted from four points: the 3rd, 6th, 12th, and 18th month after intervention. Results A total of 19 studies were included in the analysis and involved 364 patients and 14 healthy individuals. Acute SCI participants treated with bisphosphonate therapy demonstrated a trend toward less bone loss than participants who received placebos or usual care. A significant difference in BMD decline was noted between both groups at the 3rd and 12th month post-medication. The subgroup analysis failed to show the superiority of intravenous bisphosphonate over oral administration. Regarding FES training, chronic SCI patients had 5.96% (95% CI, 2.08% to 9.84%), 7.21% (95%CI, 1.79% to 12.62%), and 9.56% (95% CI, 2.86% to 16.26%) increases in BMD at the 3rd, 6th, and 12th months post-treatment, respectively. The studies employing FES ≥ 5 days per week were likely to have better effectiveness than studies using FES ≤ 3 days per week. Conclusions Our meta-analysis indicated bisphosphonate administration early following SCI effectively attenuated sublesional bone loss. FES intervention for chronic SCI patients could significantly increase sublesional BMD near the site of maximal mechanical loading.